Evaluation of the In Vitro Wound-Healing Activity of Calabrian Honeys - Governa, Paolo (Antioxidants (Basel), 2019)
The healing of skin wounds and particularly chronic wounds, such as diabetic foot ulcers, is still a clinical emergency. Despite the many therapeutic tools that are available so far, none seems to be really effective and safe. In this context, we highlighted the renewed wound healing activity of honey, a viscous aromatic and sweet food, by way of in vitro wound-healing assays, using the HaCaT cell line. Specifically, we investigated five monofloral or multifloral honeys from different Calabrian provinces using them as such or extracted (by Amberlite(®) or n-hexane and ethyl acetate). The chemical composition of honeys was ascertained by (1)H NMR spectroscopy and by the gas chromatography/mass spectrometry (GC/MS) method for volatile organic compounds (VOCs). Amongst the five tested honeys, BL1 and BL5 honeys showed the most promising healing properties. Pinocembrin, which was revealed in BL1 (multifloral) and BL5 (orange) honey samples, is a flavanol that is already known to possess interesting biological activities, including healing. This study aims to investigate how a traditional food such as honey, which is appreciated for its nutritional value and used in folk medicine, can be enhanced as an effective modern remedial to promote a multifaceted and safe healing activity for all skin wounds.